Current perspectives on world Englishes and their implications for second language teaching and learning - Alamis, Ma. Melvyn P. (2008)
This qualitative study aims to explore how teachers of English for Second Language Learning perceive the current perspectives on World Englishes. Through survey conducted with 23 teachers of English in the secondary level and 25 teachers of English in the tertiary level from four Mendiola consortium private schools in Manila, the findings found that there is yet no question of a Philippine variety of English since the spread of English on a national scale in the Philippines has just taken off. An analysis of the respondents? answers to the questionnaire showed that a majority of the teachers prefer American English as the pedagogical model in setting standards for second language teaching and learning. These results confirm that English is a language that continuously enjoys a privileged status in the Philippines and has resolutely remained a popular language, being extensively used now for a wider range of purposes. There also seems to be an implicit shared understanding that the standard variety of English is the norm.
Includes bibliographical references (page 108).